STRATEGI KOMUNIKASI PEMASARAN NTB MALL DALAM MEMASARKAN PRODUK UMKM LOKAL NTB - Zahratul Hayati; Eka Putri Paramita; Yulanda Trisula Sidarta Yohanes (Jurnal Ilmiah Mahasiswa Komunikasi (JIMaKom), 2023)
This study aims to determine the NTB Mall marketing communication strategy in promoting NTB local MSMe products. This study uses descriptive qualitative methods. Data collection is done through non-participan observation, semi-structure interviews, and documentation. Data analysis techniques are guided by Miles and Huberman consisting of merging data, data reduction, data presentation and conclusion drawing. Data analysis technique using triangulation technique. This study focuses on offline marketing communication strategy. The results of research planning activities of the NTB Mall by analyzing problems, identify audiences, formulating communication goals, and choosing media & communication channels. In the implementation activities namely through advertising, sales promotion, public relations & publicity, personal selling, direct marketing, event & experiences, mouth to mouth. Evaluation activities by measuring work and program evaluation. Keywords: Fundamental Stages of Marketing Communication Strategy, Marketing communication strategy, MSMe